Translation quality assessment of products for sale at Weasleys’ Wizard Wheezes in Harry Potter series by Lý Lan = Đánh giá chất lượng bản dịch sản phẩm ở tiệm Phù thủy Quỷ quái trong truyện Harry Potter do Lý Lan dịch - Hoàng, Thị Minh Thúy (2020)
Undeniable, not only do Harry Potter series constitute popular literary works among young audience, the books are also of great interest to theorists in evaluating translation quality. Sharing the same objective, the researcher launched the research entitled: “Translation quality of products for sale at Weasley’s Wizard Whseezes in Hary Potter series by Ly Lan”. The main method applied in the research was qualitative approach in which the researcher delved into comparing the ST and the TT. Both of the texts were analyzed along with Field, Tenor, Mode and Genre to identify Textual Function and establish profiles of the texts. After comparing the two profiles, translation errors were detected to assess translation quality and categorize translation typology. Importantly, the analysis proved that House’s model was suitable for assessing literary work. Since names of product in Harry Potter series were considered timeless texts, these labels were overtly translated. Simply put, the translation of the mentioned products did not comply with House’s hypothesis